Evaluating the efficiency of the road network for land transport in the Essaouira district (Journal of the College of Basic Education, 2023)
The original use in analyzing the structure of construction networks dates back to the period between 1960 and 1970, and there is no doubt that analyzing the infrastructure of building networks is of great importance, as it helps to communicate between networks within the country or between different countries in terms of the progress and integration of these networks. It can also be used as an indicator of the economic development that has reached the country. There are many indicators used in the geography of transportation and they differ depending on the objective of the study. We know the use of the excuse in measuring the degree of network interconnectedness between human settlements in the Essaouira district and from controlling knowledge of the extent of its efficiency due to its deficiency, and that is through Indicators.